Carrion Feeding By Spiderlings Of The Cob-Web Spider Theridion evexum (Araneae, Theridiidae) - Barrantes Montero, Gilbert (2007)
The use of carrion to feed spiderlings has never previously been observed in spiders. Here we show that the theridiid Theridion evexum Keyserling 1884 stored dead insectan prey for up to one week prior to the emergence of spiderlings from the egg sac, and continued to feed spiderlings dead prey for six weeks until spiderlings molted to the fourth instar. Spiderlings survived and molted on an experimental diet of exclusively rotten insects.